2017
DOI: 10.21608/nrmj.2017.5831
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial potency of garlic extract against certain skin pathogenic bacteria

Abstract: The antibacterial potency of garlic extract (Allium sativum) against gram positive and gram negative skin pathogenic bacteria including; Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus pyogenes, and Pseudomonas aeruginosa were studied using agar well diffusion and broth dilution assays.Agar well diffusion assay for aqueous garlic extract (AGE) was characterized with zones of inhibition ranging from 4.40 -3.80cm, 4.13 -3.57cm, 3.40 -2.67cm for S. aureus, S. epidermidis and Strep. pyogenes, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…pyogenes with diameter zones of inhibition ranging from 3.40 cm to 2.67 cm. P. aeruginosa was found to have the smallest inhibitory zones, which were 2.32 cm–1.55 cm in diameter [ 115 ]. A 31 mm inhibitory zone has been observed for both fresh local and imported garlic extracts when used against methicillin-resistant S. aureus (MRSA).…”
Section: Discussionmentioning
confidence: 99%
“…pyogenes with diameter zones of inhibition ranging from 3.40 cm to 2.67 cm. P. aeruginosa was found to have the smallest inhibitory zones, which were 2.32 cm–1.55 cm in diameter [ 115 ]. A 31 mm inhibitory zone has been observed for both fresh local and imported garlic extracts when used against methicillin-resistant S. aureus (MRSA).…”
Section: Discussionmentioning
confidence: 99%
“…pyogenes with zones of inhibition ranging from 3.40 -2.67 cm. The least inhibition zones recorded about 2.32 -1.55 cm were observed in P. aeruginosa [15]. Fresh domestic and imported garlic extract are known to play bacteriostatic activity against the methicillin-resistant Staphylococcus aureus (MRSA) with 31mm inhibition zone [16].…”
Section: Anti-bacterial Effects Of Garlic Extract (Alliums Sativum)mentioning
confidence: 99%
“…The antibacterial property of garlic extracts against several human pathogens, including Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, Salmonella spp., and Streptococcus mutans has already been described [ 28 , 29 , 30 , 31 , 32 ]. Although the activity of garlic extracts against potato phytopathogens is under-reported, a garlic WE was active against Alternaria solani [ 33 ], while chloroform, hexane, methanol [ 34 ], and water [ 22 ] extracts inhibited the growth of Rhizoctonia solani .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported inhibition of A. alternata growth by peppermint and lavender methanol-water extract [10] and peppermint essential oil [26]; however, due to a different type of extract, these findings were not reflected in the present work. The detailed results of phytopathogen growth inhibition by water-glycol extracts The antibacterial property of garlic extracts against several human pathogens, including Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, Salmonella spp., and Streptococcus mutans has already been described [28][29][30][31][32]. Although the activity of garlic extracts against potato phytopathogens is under-reported, a garlic WE was active against Alternaria solani [33], while chloroform, hexane, methanol [34], and water [22] extracts inhibited the growth of Rhizoctonia solani.…”
Section: In Vitro Evaluation Of Antimicrobial Activities Of Plant Ext...mentioning
confidence: 99%